Pengaruh Media Pembelajaran Google Classroom Terintegrasi dengan Kahoot Terhadap Minat dan Hasil Belajar Siswa Mata Pelajaran IPA Materi Siklus Air - Kholil Mujib; Muna Erawati (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Googgle Classroom learning integrated with Kahoot is online learning that utilizes two learning media into a series of fun and meaningful learning process flows for students. Google Classroom as a classroom for teachers and students that is integrated with Kahoot which is a quiz game application where each question refers to the learning material. This study aims to determine the effect of learning google classroom integrated with kahoot on the interest and learning outcomes of students in science subjects water cycle material. This is quantitative study with quasi-experimental research design (Quasi Experiment) with sample of 52 fifth grade students consisting of 26 class V A (experimental class) and 26 class V B (control class) at MI Miftahul Akhlaqiyah, Ngaliyan, Semarang City. Analysis using normality test, homogeneity, and independent t test. First, this learning can increase students' interest in learning where the calculation results are obtained t = 7.071; df= 50; p= 0.000. Second, this learning can improve learning outcomes where the calculation results are obtained t = 3.919; df= 50; p= 0.000. Thus, this learning can be used to increase student interest and learning outcomes.